2013 ISSNIP Biosignals and Biorobotics Conference: Biosignals and Robotics for Better and Safer Living (BRC) 2013
DOI: 10.1109/brc.2013.6487540
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative motor signs of head motion in cerebral palsy an analysis based on a wearable inertial human computer interface

Abstract: This paper analyzes positive and negative motor signs in people with cerebral palsy (CP). Positive motor signs are those that lead to involuntarily increased frequency or magnitude of muscle activity. Negative motor signs describe insufficient muscle activity or insufficient control of muscle activity. This work present the use of a head mounted interface based on inertial technology to assess motor signs in fourteen users with CP. The task performance is related to the impairment. The analysis of the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We measured the maximum head rotation range in the three defined planes and we found that its value in the frontal plane was 34º, 39º in the transversal, and in 28º in the sagittal. In a study presented by Raya et al, they measured the ROM while users severely affected by motor disorders controlled a computer thought their head movements [11]. They measured a ROM value of 25º in the frontal plane, 26º in the sagittal and 32º in the transversal.…”
Section: Discussionmentioning
confidence: 99%
“…We measured the maximum head rotation range in the three defined planes and we found that its value in the frontal plane was 34º, 39º in the transversal, and in 28º in the sagittal. In a study presented by Raya et al, they measured the ROM while users severely affected by motor disorders controlled a computer thought their head movements [11]. They measured a ROM value of 25º in the frontal plane, 26º in the sagittal and 32º in the transversal.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, Raya et al (2013) and Velasco et al (2016) had used the inertial interface ENLAZA for the assessment of impairment. Two metrics were proposed: the frequency of movement and the ROM of user's head.…”
Section: The Enlaza Interfacementioning
confidence: 99%
“…Two metrics for the quantification of positive and negative motor signs were proposed in previous studies: frequency of movement and ROM of user's head [8], [23]. ROM is defined as the difference between the maximum and minimum Euler angles measured in one of the anatomical planes: frontal, sagittal, or transverse (Euler angles a, ¡3, and 7).…”
Section: Assessment Of Impairmentmentioning
confidence: 99%